PERANCANGAN SISTEM INFORMASI PENJADWALAN KUNJUNGAN SALES PADA TOKO AMEERA - Rakhmat, Edy; Hadiatma, Hadiatma; Sulistiyono, Sulistiyono (Teknik Informatika Fakultas Ilmu Komputer, 2021)
The right and appropriate information system is important in managing the company. Ameera Store is a company engaged in the distribution of baby products from various kinds of principles, marketing products on credit and cash to customers. Salesmen who work at the Ameera company have an important role in distributing a product to customers. In each order, the sales and admin records data twice. Customer data and visits can only be seen manually by sales. Therefore, it is necessary to process customer data, visit frequency, order goods and billing. Currently there is no application for salesmen to remind you of every scheduled visit, this raises problems in the form of: frequent interchanges between bills and orders, so that visits are not on target and have an impact on decreasing sales value and time effectiveness. Therefore, designing an information system for scheduling sales visits becomes the basis for managing data. The method used is descriptive analytical method by means of interviews, observation and literature study. For the development of information systems applications using the waterfall methodology and modeling the business process information systems using Data Flow Diagrams (DFD). The research objective is to produce responsive web-based applications in the distribution process. The application of this system will greatly facilitate and benefit more parties, both sellers and buyers